Preliminary Study to Determine the Reference Plane of Patients with a Unilateral Cleft Lip and Palate. (November 2017) - Kim, Na-Ri; Park, Soo-Byung; Shin, Sang Min; Choi, Yong-Seok; Kim, Seong-Sik; Son, Woo-Sung; Kim, Yong-Il
Objective: The objective of this study was to determine the three-dimensional midsagittal reference planes for unilateral cleft lip and palate (UCLP) patients that can be easily applied in a clinical setting. Design: This was a retrospective analysis. Patients: There were 35 UCLP patients (25 men, 10 women; 28.1 ± 6.9 years old) in this study. Methods: With landmark's three-dimensional coordinates obtained from cone-beam computed tomography, the symmetric midsagittal reference planes were calculated by applying the ordinary Procrustes superimposition method using the original and mirror images. Procrustes analysis was also used to find the closest landmarks to the calculated symmetric midsagittal reference plane and test its compatibility with the symmetrical midsagittal reference plane. Main Outcome Measure: The three nearest landmarks to the symmetric midsagittal reference plane were Opisthion, Basion, and Nasion. Results: The averages of the sums of the squared Euclidean distance and squared Procrustes distance differences between the two configurations and shapes fabricated by the symmetrical and landmark-based midsagittal reference planes, respectively, were calculated as 1.836 ± 3.295 and 1.519 × 10 –5 ± 2.351 × 10 –5 . Conclusion: It was confirmed that the midsagittal reference planes from these selected landmarks for UCLP patients were compatible with symmetric midsagittal reference planes from the Procrustes analysis and the asymmetric measurements.